Poetics of reuse of the historical heritage: three case studies of ephemeral architecture in Venice - Zorzetto, Alessandro; Barrios Padura, Ángela; Molina Huelva, Marta; Marzo, Mauro (Journal of Architecture and Urbanism, 2022)
The archetype of the vessel, declined ontologically as heterotopia and etymologically as trait d’union of a community, becomes the pretext to propose the restoration of Venice’s citizenship through a “poetics of reuse”. The relationship between ephemeral architecture and historical heritage is analysed according to the three criteria identified by Pierre Pinon. The concept of reutilisation is declined through building materials. Reconversion is identified through examples of radical change of use of historic military buildings. Reappropriation is associated with the temporary expansion of the potential of public space through architectural installations. Case studies corresponding to each category are identified, and from the primary sources the three-dimensional redesign of these projects is contextualised in the historical surroundings, in order to deduce considerations regarding the relationship between the two frameworks. Since the case studies are very extensive and rather heterogeneous, the novelty lies in the transversal reading approach that returns the Biennale’s magnificent centenary activity directly to the city and its inhabitants, subverting the negative connotation that cultural tourism has acquired on the island. The research aims to create an atlas of ephemeral architecture, define a taxonomy and draw up a document containing guidelines for future experiences of ephemeral architecture in the city.